Γ-Cyclodextrin Increases Hydrolysis of Gangliosides by Sialidase from Arthrobacter ureafaciens: Hydrolysis of Gangliosides. (28th December 2008) - Mitsumori, Rie; Kato, Tomohisa; Hatanaka, Kenichi
Abstract : Sialidase is a ubiquitous enzyme that catalyzes the hydrolytic removal of terminal sialic acid residues from oligosaccharides in glycolipids and glycoproteins. Ganglioside GM1 has been usually found to be resistant to various sialidases. Arthrobacter ureafaciens sialidase has been reported to remove sialyl residues of ganglioside GM1 in the presence of bile salts. However, bile salts are difficult to be removed, and disturb HPTLC analysis. Usingγ -cyclodextrin (γ -CD) as a novel additive agent, ganglioside GM1 was efficiently hydrolyzed to asialo-GM1 by A. ureafaciens sialidase.